Cyclic Octapeptides Composed of Two Glutathione Units Outperform the Monomer in Lead Detoxification - Sauser, Luca; Kalvoda, Tadeáš; Kavas, Ayça; Rulíšek, Lubomír; Shoshan, Michal S (ChemMedChem, 2022)
A rationally-designed scaffold of cyclic octapeptides composed of two units of the natural tripeptide glutathione (GSH) was optimized to strongly and selectively capture toxic lead ions (Pb(II)). Using state-of-the-art computational tools, a list of eleven plausible peptides was shortened to five analogs based on their calculated affinity to Pb(II) ions. We then synthesized and investigated them for their abilities to recover Pb-poisoned human cells. A clear pattern was observed from the in vitro detoxification results, indicating the importance of cavity size and polar moieties to enhance metal capturing. These, together with the apparent benefit of cyclizing the peptides, improved the detoxification of the two lead peptides by approximately two folds compared to GSH and the benchmark chelating agents against Pb poisoning. Moreover, the two peptides did not show any toxicity and, therefore, were thoroughly investigated to determine their potential as next-generation remedies for Pb poisoning.
Keywords: olovo; Peptides; Chelating Agents; antioxidancia; glutathion; Glutathione; Chelates; Lead; chelátory; lidé; Bioinorganic chemistry; Antioxidants; Humans